Respuesta :

Answer:

a.  13xyz + 9 + 2xyz + 3

13xyz+2xyz+ 9+3 ( combine like terms)

15xyz+12

b. 6ab + (–2ab) + 4 + 6

6ab-2ab+4+6

4ab+10

Answer:

a. 13xyz + 9 + 2xyz + 3

Combine the coefficents of the like monomials.

(13 + 2 = 15)

15xyz + 9 + 3

Add the constants (9 + 3 = 12).

Answer: 15xyz + 12

b. 6ab + (–2ab) + 4 + 6

Combine the coefficents of the like monomials.

[6 + (–2) = 4]

4ab + 4 + 6

Add the constants (4 + 6 = 10).

Answer: 4ab + 10

Step-by-step explanation:

straight from Penn